Robotic and open partial nephrectomy for intermediate and high complexity tumors: a matched-pairs comparison of surgical outcomes at a single institution. (3rd July 2020) - Abedali, Zain A.; Monn, M. Francesca; Huddleston, Patrick; Cleveland, Brent E.; Sulek, Jay; Bahler, Clinton D.; Foster, Richard S.; Koch, Michael O.; Mellon, Matthew J.; Kaimakliotis, Hristos Z.; Cary, Clint; Bihrle, Richard; et al.
Abstract: Objective: To compare peri-operative factors and renal function following open partial nephrectomy (OPN) and robotic partial nephrectomy (RPN) for intermediate and high complexity tumors when controlling for tumor and patient complexity. Methods: A retrospective review of 222 patients undergoing partial nephrectomy was performed. Patients with intermediate (nephrometry score NS 7–9) or high (NS 10–12) complexity tumors were matched 2:1 for RPN:OPN using NS, Charlson Comorbidity Index (CCI), and BMI. Patient demographics, peri-operative values, renal function, and complication rates were analyzed and compared. Results: Seventy-four OPN patients were matched to 148 RPN patients with no difference in patient demographics. Estimated blood loss in OPN patients was significantly higher (368.5 vs 210.5 mL, p  < 0.001) as was transfusion rate (17% vs 1.6%, p  < 0.001). Warm ischemia time was longer in OPN (25.5 vs 19.7 min, p  = 0.001) while operative time was reduced (200.5 vs 226.5 min, p  = 0.010). RPN patients had significantly shorter hospitalizations (5.3 vs 3.0 days, p  < 0.001). GFR decrease after one month was not statistically significant (12.9 vs 6.6 ml/min, p  = 0.130). Clavien III–V complications incidence was higher for OPN compared to RPN although not significantly (20.3% vs 10.8%, p  = 0.055). Conclusion: When matching for tumor and patient complexity, RPN patients had fewer high grade post-operative complications, decreased blood loss, and shorter hospitalizations. RPN is a safe option for patients with intermediate and high complexity tumors.